Cross-species analysis of apical asparagine-rich protein of Plasmodium vivax and Plasmodium knowlesi - Muh, F.; Ahmed, M.A.; Han, J.H.; Nyunt, M.H.; Lee, S.K.; Lau, Y.L.; Kaneko, O.; Han, E.T. (Nature Publishing Group, 2018)
The Plasmodium falciparum apical asparagine (Asn)-rich protein (AARP) is one of malarial proteins, and it has been studied as a candidate of malaria subunit vaccine. Basic characterization of PvAARP has been performed with a focus on its immunogenicity and localization. In this study, we further analyzed the immunogenicity of PvAARP, focusing on the longevity of the antibody response, cross-species immunity and invasion inhibitory activity by using the primate malaria parasite Plasmodium knowlesi. We found that vivax malaria patient sera retained anti-PvAARP antibodies for at least one year without re-infection. Recombinant PvAARP protein was strongly recognized by knowlesi malaria patients. Antibody raised against the P. vivax and P. knowlesi AARP N-termini reacted with the apical side of the P. knowlesi merozoites and inhibited erythrocyte invasion by P. knowlesi in a concentration-dependent manner, thereby suggesting a cross-species nature of anti-PvAARP antibody against PkAARP. These results can be explained by B cell epitopes predicted in conserved surface-exposed regions of the AARP N-terminus in both species. The long-lived anti-PvAARP antibody response, cross-reactivity, and invasion inhibitory activity of anti-PvAARP support a critical role of AARP during the erythrocyte invasion and suggest that PvAARP induces long-lived cross-species protective immunity against P. vivax and P. knowlesi.